Developing Visible Thinking and Motivation Through the Curricular Design of an Escape Room in Higher Education - Bilbao-Quintana, Naiara (2021)
Introduction. The term escape room has undergone a notable evolution in recent years, extending its presence to areas not only recreational but also business or educational. The defining traits (overcoming obstacles, problem-solving, teamwork, time management...) have proven to be valid in business and education. This study presents the pedagogical design of an escape room based on visible thinking and analyses its effect on the motivation and cognitive processes of higher education students. Method. For this purpose, a quasi-experimental research with pretest/post-test was conducted, and it was evaluated whether the instructional design of the escape room was adequate to enhance the learning of the 238 students, whether it was motivating, and whether it contributed to the development of cognitive processes. We used two structured questionnaires with multiple-choice questions and one questionnaire with open-ended questions. We also applied a mixed method for quantitative and qualitative data collection and analysis. Results. The results show that the students consider the characteristics of the escape room and the organization of its elements to be of high quality; they also show that the curricular design of the escape room enhances students’ learning. In particular, the students consider that they have developed group thinking, critical thinking, and the activation of prior knowledge through the escape room and have found it a motivating experience. Conclusions. The use of the escape room in educational environments has a high educational potential. This is not only because it encourages the development of higher-order cognitive processes but also because it contributes to teamwork, self-regulation, and student motivation. However, it must be designed as a significant part of the didactic program, taking special care in the development of competences and thinking.